2010
DOI: 10.1007/s11046-010-9365-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Heat Treatments and Disinfectants on the Survival of Prototheca zopfii

Abstract: Bovine mastitis caused by the yeast-like alga Prototheca zopfii represents a serious veterinary problem and may result in heavy economic losses to particular dairy farms. The purpose of this study was to evaluate the survival of 50 isolates of P. zopfii in milk subjected to different heat treatments and the survival of further 106 P. zopfii isolates after exposure to three classes of teat disinfectants: iodine (Dipal), quaternary ammonium compounds (Teat), and dodecylbenzenesulphonic acid (Blu-gard). Of the 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
2
30
2
Order By: Relevance
“…The longer the incubation period, the higher the concentration of sanitizer needed to prevent reproduction of the P. zopfii isolates. Lassa et al (2011) evaluated the effectiveness of 3 sanitizers at preventing reproduction of P. zopfii; however, in contrast to the present study, they reported that the efficiency of the sanitizer depends more on the concentration used than on the incubation period.…”
Section: Resistance Profile Of Prototheca Spp To Sanitizers Determincontrasting
confidence: 80%
See 4 more Smart Citations
“…The longer the incubation period, the higher the concentration of sanitizer needed to prevent reproduction of the P. zopfii isolates. Lassa et al (2011) evaluated the effectiveness of 3 sanitizers at preventing reproduction of P. zopfii; however, in contrast to the present study, they reported that the efficiency of the sanitizer depends more on the concentration used than on the incubation period.…”
Section: Resistance Profile Of Prototheca Spp To Sanitizers Determincontrasting
confidence: 80%
“…Furthermore, in response to exposure to the IAA/HRP, cellular viability and colony production of P. zopfii were reduced. In another study, the use of teat sanitizers was evaluated and, in contrast to the present study, iodine was the most efficient sanitizer (Lassa et al, 2011).…”
Section: Resistance Profile Of Prototheca Spp To Sanitizers Determincontrasting
confidence: 64%
See 3 more Smart Citations